Hubungan Rasio Neutrofil Limfosit (RNL) d engan Status Merokok Pada Kanker Paru - Indah Sari, Fitri; Setyawan, Ungky; Destyana, Dita (Jurnal Klinik dan Riset Kesehatan, 2023)
Background: The high mortality rate is influenced by several risk factors, one of which is smoking which is currently the main risk factor for lung cancer. NLR and from peripheral whole blood can be evidence of systemic inflammation and cancer prognostic index. Aim: The purpose of this study was to determine the characteristics of lung cancer patients based on age, sex, smoking status and NLR in RSSA Malang and the relationship between RNL and smoking status of lung cancer patients in RSSA Malang Methods: This research method is an analytic observational study using a cross-sectional research design approach. The population of this study were all patients who were diagnosed lung cancer who were treated at RSUD Dr. Saiful Anwar Malang City from January 2021 to March 2022. The sample data is secondary data taken from the medical records of 40 lung cancer patients at RSSA Malang. Results: The results showed that the characteristics of the subjects were dominated by age <60 years where the smoking status was more recorded in this study with a total of 22 with male sex being more dominant than women with a number of 24 and more recorded as smokers. In this study, NLR values ​​>3.53 were more commonly found in lung cancer patients. The mean in smokers has a higher NLR value of 4.821 ± 3.88 while in non-smokers it has a value of 4.253 ± 3.73. Conclusion: There is no significant difference and relationship between NLR values ​​in smokers and non-smokers.